The Impact of Chitosan and Tithonia Diversifolia Compost on the Growth and Yield of Peanut Plants (Arachis hypogaea L.) - Zahanis Zahanis; Widodo Haryoko; Ira Fitri Rahmadani; Devi Purnamasari (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
This study aims to investigate the combined impact of Chitosan and Tithonia (Tithonia diversifolia) Compost on the Growth and Yield of Peanut Plants (Arachis hypogaea L.). A factorial randomized block design (RBD) was utilized for the experiment. The first factor was Tithonia compost in quantities of 0 tons/ha-1, 5 tons/ha-1, and 10 tons/ha-1. The second factor was Chitosan, applied at three dosage levels: 0 ml/l water, 3 ml/l water, and 6 ml/l water. The results suggest that the use of Tithonia compost effectively enhances plant height, flowering age, harvest age, 100-seed weight, and dry pod weight per hill when applied at a dose of 10 tons/ha. Furthermore, Chitosan administration was found to increase the number of effective root nodules when used at a concentration of 6 ml/l water. The interaction between Tithonia compost and Chitosan also resulted in an extended flowering life and an increase in dry pod weight per hill of peanut plant. Based on these findings, we recommend using 10 tons/ha of Tithonia compost and 3 ml/l water of Chitosan in peanut cultivation for optimal results.